A flying life John Duigan and the first Australian aeroplane - Crotty, David (Museum Victoria, 2010)
The flying career of John Robertson Duigan spanned just a decade from 1908 to 1918. One hundred years ago he built and successfully flew the first aeroplane made in Australia using only photographs, journal articles and an unreliable textbook as his guides. He was the first Australian to fly a powered Australian-made aeroplane in Australia.